2013
DOI: 10.1509/jppm.11.158
|View full text |Cite
|
Sign up to set email alerts
|

Are All Proximity Effects Created Equal? Fast Food near Schools and Body Weight among Diverse Adolescents

Abstract: Prior research has demonstrated that the proximity of fast-food restaurants to schools is related to higher youth body weight and also suggests that this relationship may be stronger in urban areas. Research also suggests that some segments of youth may be more vulnerable to this relationship than others. The authors investigate the relationship of fast-food proximity to middle and high schools and adolescent weight outcomes, with a focus on understanding intra-urban differences across groups defined by ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 54 publications
0
78
0
1
Order By: Relevance
“…Further, recent evidence finds that there is a greater adverse effect on diet quality from fast-food consumption among low- versus high-income children and adolescents and among black versus white adolescents (Powell and Nguyen, 2013). Evidence from California also shows that black and Hispanic students at low-income and urban schools have significantly higher associations between body weight and proximity to fast-food restaurants compared to white students at higher-income, nonurban schools (Grier and Davis, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Further, recent evidence finds that there is a greater adverse effect on diet quality from fast-food consumption among low- versus high-income children and adolescents and among black versus white adolescents (Powell and Nguyen, 2013). Evidence from California also shows that black and Hispanic students at low-income and urban schools have significantly higher associations between body weight and proximity to fast-food restaurants compared to white students at higher-income, nonurban schools (Grier and Davis, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Five articles examined nutritional content and frequency of food and beverage advertisements (ads) on TV (Abbatangelo-Gray, Byrd-Bredbenner, & Austin, 2008;Bell, Cassady, Culp, & Alcalay, 2009;Castetbon, Harris, & Schwartz, 2012;Fleming-Milici, Harris, Sarda, & Schwartz, 2013;Kunkel, Mastro, Ortiz, & McKinley, 2013), four of which were focused on TV ads to those younger than 18 years (Bell et al, 2009;Castetbon et al, 2012;Fleming-Milici et al, 2013;Kunkel et al, 2013). Five articles focused on food store placement (Grier & Davis, 2013;Inagami, Cohen, Finch, & Asch, 2006;Moore, Diez Roux, Nettleton, & Jacobs, 2008;Powell, Auld, Chaloupka, O'Malley, & Johnston, 2007;Rose et al, 2009), of which two focused on fast-food restaurant proximity to schools (Grier & Davis, 2013;Powell et al, 2007) and three focused on grocery/supermarket proximity to households (Inagami et al, 2006;Moore et al, 2008;Rose et al, 2009). Single articles examined these topics: prevalence of Latino actors and the types of ads or products they advertised during children's TV programming (Bang & Reece, 2003), types of health ads appearing in women-oriented magazines (Duerksen et al, 2005), product preferences among Latino and non-Latino consumers (Moskowitz et al, 2004), and 1 Deemed not relevant if the study did not encapsulate the marketing mix or if the article included Latinos but did not include a comparison group.…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…Six articles analyzed RFS placement, characteristics, and availability and quality of food products (Emond et al, 2012;Grier & Davis, 2013;Inagami et al, 2006;Moore et al, 2008;Powell et al, 2007;Rose et al, 2009). Four used individual and neighborhood characteristic data to examine RFS distribution in proximity to homes (Moore et al, 2008), point of grocery purchases (Inagami et al, 2006), and schools (Grier & Davis, 2013;Powell et al, 2007). Two articles analyzed the availability, quality, and/or placement of specific products in supermarkets and smaller corner stores, called tiendas (Emond et al, 2012;Rose et al, 2009).…”
Section: Rose Dmentioning
confidence: 99%
“…Fast food restaurants tend to be more concentrated near schools attended by Latino youth, and fast food availability near schools has been associated with greater fast food intake (Babey et al, 2009) and higher BMI among Latino and Black youth (Grier and Davis, 2013; Sánchez et al, 2012). Prior research has observed greater fast food consumption among Latino children than other race/ethnic groups (Taveras et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Children from disadvantaged and racial/ethnic minority backgrounds are more likely to use active school transport than their White counterparts (Babey et al, 2009; Martin et al, 2007; McDonald, 2008), and schools attended by Black and Latino students tend to have a greater concentration of fast food outlets nearby compared to schools attended by mostly White children (Forsyth et al, 2012; Grier and Davis, 2013; Kwate and Loh, 2010; Sánchez et al, 2012; Sturm, 2008). Racial/ethnic differences in fast food environments near schools may lead to greater consumption of fast food among racial minority children who engage in active school transport.…”
Section: Introductionmentioning
confidence: 99%